A Study on the Behavior of Students from Broken Home Backgrounds at Rantau Utara High School - Wijaya, Ade Putri Wijaya, Putri; Hasibuan, Ali Daud (Tarbiyah Wa Ta'lim: Jurnal Penelitian Pendidikan dan Pembelajaran, 2024)
Family is a fundamental entity in individual development, and family background can influence student behavior and academic performance. This research aims to investigate the impact of separated families on student behavior in a school environment. Using a qualitative approach, the researchers analyzed the determining factors associated with the behavior of students from separated families. The study involved a sample of 10 eleventh-grade students from broken homes, focusing on family interaction, emotional support, and personality. Data were collected through in-depth interviews and observations. The results of the study showed a correlation between separated family backgrounds and student learning behavior, revealing significant variations in students' responses and coping strategies to the situation. Factors such as social support, parental education, and the availability of family resources were also found to play important roles in shaping student behavior